PENINGKATAN PEMAHAMAN ANAK USIA DINI TENTANG PENGGUNAAN GADGET MELALUI KEGIATAN EDUKATIF - Dewi Susanawati; Delvia Putri Dinanda; Pipit Nuri Mulyaningtias; Rizka Fajrina S (Penerbit Widina, Widina Media Utama, 2026)
The rapid development of digital technology has made gadgets an integral part of young children's daily lives. Uncontrolled gadget use may negatively affect children's development; however, when used appropriately, gadgets can serve as effective educational tools. This community service program aimed to improve young children's understanding of responsible and educational gadget use. The program was conducted at PAUD Amanah Bunda and involved 20 children aged 5-6 years. The methods included educational presentations using visual media and videos, tablet based educational games, interactive question-and-answer sessions, and observations conducted before and after the activities. The results showed an improvement in children's understanding of the benefits, risks, and proper use of gadgets. Participants also demonstrated increased engagement and focus during the activities. Children's developmental achievement improved from the Beginning Development (BD) category to the Developing as Expected (DE) category, with an overall success rate of 95%. These findings indicate that digital media-based educational activities are effective in promoting positive gadget-use awareness among young children. ABSTRAKPerkembangan teknologi digital menjadikan gadget sebagai bagian dari kehidupan sehari-hari anak usia dini. Penggunaan gadget yang tidak terkontrol dapat berdampak negatif terhadap perkembangan anak, namun jika dimanfaatkan secara tepat dapat menjadi media pembelajaran yang efektif. Kegiatan pengabdian kepada masyarakat ini bertujuan meningkatkan pemahaman anak usia dini mengenai penggunaan gadget secara bijak dan edukatif. Kegiatan dilaksanakan di PAUD Amanah Bunda dengan melibatkan 20 anak usia 5-6 tahun. Metode yang digunakan meliputi penyampaian materi melalui media visual dan video edukasi, permainan edukatif berbasis tablet, tanya jawab interaktif, serta observasi sebelum dan sesudah kegiatan. Hasil menunjukkan adanya peningkatan pemahaman anak mengenai manfaat, risiko, dan penggunaan gadget yang tepat. Anak juga menunjukkan peningkatan keaktifan dan fokus selama kegiatan berlangsung. Perkembangan anak meningkat dari kategori Mulai Berkembang (MB) menjadi Berkembang Sesuai Harapan (BSH) dengan tingkat keberhasilan mencapai 95%. Kegiatan edukatif berbasis media digital terbukti efektif dalam menanamkan pemahaman penggunaan gadget yang positif pada anak usia dini.